Konstruksi Sosial Keagamaan Islam di Masyarakat Pada Masa Pandemi Covid-19 - Luky Septian; Agus Machfudz Fauzi (Purwadita : Jurnal Agama dan Budaya, 2022)
The theoretical conception in this study uses the social construction theory of Peter L. Beger with three components, namely externalization, objectivation, and internalization. The research approach used is qualitative with descriptive type, and data collection through primary and secondary data. The purpose of this study is to reveal and explain the social reality of Islamic religious behavior and values in society during the COVID-19 pandemic. The results obtained are that there is a socio-religious construction in society during the pandemic, this can be seen by the construction of religious values that change people's lives to adjust to the current situation.